Knowledge of burn first aid among caregivers in pediatric clinic of Hospital Universiti Sains Malaysia - Shafikah, Nurul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
Burn first aid is a very important step in the process of cooling the burn. If no initial treatment, burn victims might faced many problems and complications throughout their recovery such as develop severe infection. The objective of this study is to determine the knowledge of burn first aid among caregivers in Pediatric Clinic of Hospital Universiti Sains Malaysia (USM). A cross-sectional descriptive study was used in this study. Purposive sampling technique was used to select the caregivers in Pediatric Clinic. A total of 233 caregivers comprimising female was the majority of the respondents which was 177 and male was only 56 were answered the questionnaire provided. The collected data were analysed by using descriptive statistics (mean, frequency, and percentage) and inferential statistics (chi-square and independent t-test). A total of 120 respondents were categorised in good level of knowledge and 113 respondents had poor level of knowledge. There was a significant difference between demographic data with the knowledge of burn first aid for the burn first aid training (p= 0.000), but no significant difference between the level of knowledge with gender (p= 0.797) or previous burn injury (p= 0.097). While there no significant association between age (p= 0.055), educational level (p= 0.368), or source of information with the knowledge of burn first aid. The knowledge level of burn first aid was high, but finding from this study shows the need for further enhancement to maximise the knowledge regarding burn first aid among caregivers. In conclusion, education for caregivers, including demonstrations regarding first aid of burn is needed to prevent further injury or any serious complication.